EXPLORING DIGITAL TRANSFORMATION OPPORTUNITIES FOR MSMES: A PHENOMENOLOGICAL STUDY IN THE EASTERN INDONESIAN CULINARY SECTOR - Hasim La Baaji; Serpian Serpian (Journal of Management Small and Medium Enterprises (SMEs), 2026)
Digital transformation offers substantial opportunities for Micro, Small, and Medium Enterprises (MSMEs) in Eastern Indonesia; however, its implementation remains constrained by infrastructural limitations, low levels of digital literacy, and cultural tensions. This study explores the lived experiences of culinary MSME actors as they navigate the complexities of digitalization, with the aim of understanding how they interpret, negotiate, and adapt to technological change. Adopting a phenomenology-based ethnographic approach, the research draws on in-depth interviews and documentation to capture rich, contextualized accounts of participants’ digital experiences. The findings indicate that digital transformation within these enterprises does not constitute a linear or fully autonomous shift toward modernization. Instead, it represents a process of “conditioned becoming modern,” characterized by constrained agency shaped by infrastructural barriers, selective adoption of digital tools, and strong dependence on family and community networks for knowledge exchange and skill acquisition. These results challenge the universal applicability of diffusionist perspectives, particularly Rogers’ Diffusion of Innovation theory, which tends to assume relatively homogeneous pathways of technology adoption. The study therefore underscores the importance of context-sensitive policies that integrate local cultural values, social structures, and infrastructural realities to foster inclusive and sustainable digital transformation among MSMEs. Keywords: Digital Transformation; MSMEs; Phenomenology